HUBUNGAN INDEKS MASSA TUBUH TERHADAP KADAR HEMOGLOBIN DAN HEMATOKRIT SEBAGAI PENANDA ANEMIA PADA SISWI DI SMA NEGERI 1 KALIANGET: RELATIONSHIP BETWEEN BODY MASS INDEX AND HEMOGLOBIN AND HEMATOCRITE LEVELS AS MARKERS OF ANEMIA IN FEMALE STUDENTS AT STATE SENIOR HIGH SCHOOL 1 KALIANGET - Ajie, Devy Verliantina; Herawati, Dheasy; Wijaya, Halik (Jurnal SainHealth, 2025)
Iron deficiency anemia is a condition of decreased health quality that is susceptible to adolescent girls. Someone who has a BMI below normal has a risk of iron metabolism disorders due to indications of low micronutrient intake. Iron deficiency causes low hemoglobin levels because iron is an important substance in the hemoglobin molecule. Hct examination is carried out as a simple screening for anemia and accompanies the results of the Hb examination to prove the level of accuracy of the diagnosis. This study aims to investigate the relationship between BMI and hemoglobin and hematocrit levels in adolescents in a population in the Kalianget Health Center area with the sample determined being female students at SMA Negeri 1 Kalianget, Sumenep. The design used in this study was analytical with a cross-sectional approach. Capillary blood sampling of 96 female students was carried out using the POCT method to measure Hb and Hct. In this study, a bivariate analysis was conducted to determine the relationship between body mass index (BMI) and Hb and Hct using the chi square test. The results of the Chi-square test analysis, a p value of 0.000 <0.05 was obtained for the relationship between BMI and Hb and a p value of 0.001 <0.05 for the relationship between BMI and Hct. Conclusion of this research is There is a relationship between BMI and Hb and Hct of students at SMAN 1 Kalianget.